2021
DOI: 10.1016/j.ajhg.2021.02.014
|View full text |Cite|
|
Sign up to set email alerts
|

Estimation of non-additive genetic variance in human complex traits from a large sample of unrelated individuals

Abstract: Non-additive genetic variance for complex traits is traditionally estimated from data on relatives. It is notoriously difficult to estimate without bias in non-laboratory species, including humans, because of possible confounding with environmental covariance among relatives. In principle, non-additive variance attributable to common DNA variants can be estimated from a random sample of unrelated individuals with genome-wide SNP data.Here, we jointly estimate the proportion of variance explained by additive (ℎ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 50 publications
6
99
0
Order By: Relevance
“…For example, the rs11020521 and rs11020522 haplotype pair exhibited an interaction with sign reversal where each variant individually has no effect or is weakly positive, while the joint haplotype is much more significant in the opposite direction (Figure 4H). These results support other synthetic, eQTL and complex trait studies that have identified non-additive regulatory effects ( 20, 3436 ) and find that 14.7% of significant haplotype effects (only 0.91% of all tests) have evidence of non-additivity.…”
Section: Resultssupporting
confidence: 89%
“…For example, the rs11020521 and rs11020522 haplotype pair exhibited an interaction with sign reversal where each variant individually has no effect or is weakly positive, while the joint haplotype is much more significant in the opposite direction (Figure 4H). These results support other synthetic, eQTL and complex trait studies that have identified non-additive regulatory effects ( 20, 3436 ) and find that 14.7% of significant haplotype effects (only 0.91% of all tests) have evidence of non-additivity.…”
Section: Resultssupporting
confidence: 89%
“…However, the increase in power is still expected to be substantial from additive components that are usually considered major in a genetic architecture, with effect sizes highly similar across populations ( Wojcik et al, 2019 ). Additionally, currently the contribution from epistasis or G × E components to most trait variability is estimated to be relatively small ( Wang et al, 2019 ; Dahl et al, 2020 ; Hivert et al, 2021 ). For variants with heterogeneous effect sizes per ancestry, other local ancestry-aware regression methods could potentially improve the power of detection in admixed populations ( Atkinson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…An error term is sometimes included in Equations 1 and 2 or is otherwise incorporated into the V E term.6 In humans, V D and V I do not appear to influence phenotypic variance to a great degree for most quantitative traits(Hivert et al 2020), meaning that h 2 and H 2 estimates should generally converge.…”
mentioning
confidence: 99%